Evolusi Aktual Aktivitas Urban Tourism di Kota Bandung dan Dampaknya Terhadap Pembentukan Tempat-Tempat Rekreasi - Wardhani, Apriliana Dyah (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Urban tourism in South-East Asia has been increasing significantly; the number of visitors rose from 36,1 million in the year 2000 to 69,6 million in 2010. In general, tourism contributes 4,6% of Asean’s income, hence it is included in its development strategy. The study is based on the phenomenon that modernization tends to shift tourism activities in Bandung City, West Java from cultural-historical tourism towards more shopping-culinary activities which are basically consumption; an evolution on urban tourism. The study examines how the shift has affected the development of various new tourist attractions, the pattern of their development and the affecting factors using qualitative-rationalistic method through in-depth interviews. The study found that many facilities, which before had only served as supporting services for tourism, such as restaurants, shopping malls and entertainment services have indeed shifted to become the main attraction of tourism in Bandung City.